THU0022 Kir3Dl1 (nkb1) and cd94 expression on peripheral blood t cells, nk cells and nkt cells in behcet's disease. (1st June 2001) - Saruhan Direskeneli, G; Uyar, FA; Cefle, A; Celebi Onder, S; Inanc, M; Ocal, L; Gul, A
Abstract : Background: Behcet's disease (BD) is strongly associated with HLA-B51. However, the role of HLA-B51 in the pathogenesis still remains to be elucidated. We have recently identified a weak association of HLA-B*2702 with BD. HLA-B51 and B*2702 shares one of the 5 Bw4 motifs at positions 77–83, which interacts with a group of recently described receptors on mainly NK cells, but also CD8 + and gamma-delta T cells. Interaction of HLA-B molecules with one of these receptors, killer immunoglobulin-like receptor (KIR) on NK, NKT, CD8 + and/or gamma/delta T cells may be one of the pathogenic mechanisms involved in BD. Objectives: We aimed to investigate the KIR3DL1 and CD94 (a C-type lectin receptor which mainly interacts with HLA-E) expression in BD. Methods: The study group consisted of 51 patients, who fulfil the International Study Group Criteria, and 32 HLA-Bw4 motif matched healthy controls. All patients and controls were already HLA-typed, and they were selected and grouped according to the presence and number of the shared Bw4 epitope. All of the patients were receiving treatment and their disease activity was under control. Expression patterns of CD3, CD16, CD56, CD45, CD14, KIR3DL1 (NKB1) and CD94 in peripheral blood leukocytes were determined with fluorescent-labelled monoclonal antibodies using flow cytometry. Results: The percentage of CD3 + cells was found to be increased in BD patients, but there was no significant difference in NK (CD56 + /CD16 +, CD3-/CD56 + ) and NKT (CD3 + /CD56 + ) cells between BD patients and controls. The distribution of KIR3DL1 receptor did not show any significant difference in patients, however we observed a significant increase of CD94 expression in T cells, NK and NKT cells. Subgroup analysis in patients carrying 1, 2 or no copies of the shared Bw4 motif also did not reveal any effect on the expression of KIR3DL1 and CD94. Conclusion: We did not observe any difference in the expression of KIR3DL1 receptors in this group of BD patients compared with healthy HLA-Bw4 motif matched controls. Increased CD94 expression in peripheral blood T cells, NK and NKT cells of BD patients needs to be confirmed and analysed further. This study was supported by the Research Fund of the University of Istanbul (1076).